Drastic Reductions in Mental Well-Being Observed Globally During the COVID-19 Pandemic: Results From the ASAP Survey - Wilke, Jan; Hollander, Karsten; Mohr, Lisa; Edouard, Pascal; Fossati, Chiara; González-Gross, Marcela; Sánchez Ramírez, Celso; Laiño, Fernando; Tan, Benedict; Pillay, Julian David; Pigozzi, Fabio; Jimenez-Pavon, David; et al. (Frontiers in Medicine, 2021)
Most countries affected by the COVID-19 pandemic have restricted public life in order to control the contagion. However, the health impact of confinement measures is unclear. In a total of 14,975 individuals from 14 countries, we performed a multinational survey investigating changes in mental and physical well-being (MWB/PWB). MWB, as measured by the WHO-5 questionnaire, decreased considerably during restrictions (68.1±16.9 to 51.9±21.0 points). Whereas 14.2% of the participants met the cut-off for depression screening pre-restrictions, this share tripled to 45.2% during restrictions. Factors associated with clinically relevant decreases in MWB were: female sex (odds ratio/OR = 1.20, 95% CI: 1.11 to 1.29); high physical activity levels pre-restrictions (OR = 1.29, 95% CI 1.16 to 1.42); decreased vigorous physical activity during restrictions (OR = 1.14, 95% CI: 1.05 to 1.23); and working (partially) outside the home vs. working remotely (OR = 1.29, 95% CI: 1.16 to 1.44 / OR = 1.35, 95% CI: 1.23 to 1.47). Reductions were also seen for PWB. Scores in the SF-36 bodily pain subscale decreased from 85.8±18.7% pre-restrictions to 81.3±21.9% during restrictions. Clinically relevant decrements of PWB were associated with female sex (OR= 1.62, 95% CI: 1.50 to 1.75), high levels of public life restrictions (OR = 1.26, 95% CI: 1.18 to 1.36), and young age (OR = 1.10, 95% CI: 1.03 to 1.19). Lockdowns during the COVID-19 pandemic may have had substantial adverse public health effects. The development of interventions mitigating losses in MWB and PWB is paramount when preparing for forthcoming waves of COVID-19.